THE ANALYSIS STUDY OF MANAGEMENT AND OUTCOMES OF CORNEAL DISEASE: A COMPREHENSIVE SYSTEMATIC REVIEW - Utomo, Siswo; Jamilah, Esa Mahirotul (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: A group of conditions affecting the cornea are referred to as corneal disease. These diseases affect over 10 million people worldwide and are caused by various clinical diseases, such as traumatic injuries, chemical burns, infections, and iatrogenic reasons. Causes include bacterial keratitis, fungal keratitis, Herpes Simplex Keratitis (HSK), trachoma, dry eye disease, keratoconus, ophthalmia neonatorum, and non-infectious neonatorum. The causes of corneal disease affect how they are managed. The outcomes of these interventions vary. The aim: This study aims to determine the management and outcomes of corneal disease. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SAGEPUB, and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 1358 articles, whereas the results of our search on SAGEPUB brought up 1823 articles, and our search on ScienceDirect brought up 6091 articles. In the end, we compiled 6 papers, 3 of which came from PubMed, 2 of which came from ScienceDirect, and 1 of which came from SagePub. We included six research that met the criteria. Conclusion: In conclusion, surgical management shows good outcomes in controlling the corneal diseases. It can also maintain structural integrity of cornea and contribute to lowering blindness worldwide.